The festival of insignificance : a novel - Kundera, Milan; Asher, Linda (London: Faber & Faber, 2015)
"An enchanting new novel from one of the most distinguished writers of our time, an altogether serious comedy that is the synthesis and culmination of his oeuvre"--
Keywords: FICTION / Literary; FICTION / General